Mode matching for efficient laser diode to single mode fiber coupling - Fadhali , author; Saktioto, author; Zainal J, author; Munajat Y, author; Ali J, author; Abdul Rahman R, author; International Workshop and Conference on Photonics and Nanotechnology (2007 : Pattaya, Thailand) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL